Collaborative Governance dalam Pemberdayaan Masyarakat Penyandang Disabilitas di Kabupaten Pati - Rohman, Ahmad Mutawakkilir; Hamidah, Kamilia (Mafa Press, 2024)
This study aims to analyze the implementation of collaborative governance in the empowerment of persons with disabilities in Pati Regency. Using a qualitative descriptive approach and field research methods, the study explores how the collaboration between local government, the Indonesian Disability Association (PPDI), and the local community contributes to improving the quality of life and welfare of persons with disabilities. The results show that this collaboration significantly enhances accessibility, productivity, and participation of persons with disabilities in various empowerment programs. However, the involvement of the private sector in collaborative forums remains a challenge that must be addressed to create broader synergy. In conclusion, collaborative governance is an effective approach for creating inclusive policies and empowering persons with disabilities, but more support from the private sector is needed.